Teachers' perspectives on applying online learning tools through learning management system: The need for an online Malay language teaching module - Sulong, M. Badrul Hisyam; Nasir, M. Khalid M; Mohamad, Wan Muna Ruzanna Wan (Journal of Education and e-Learning Research, 2024)
This study examines Malay language teachers' perceptions of using Google tools in their online teaching in primary schools. It uses a basic interpretative research methodology to investigate the perspectives of six primary school Malay language teachers from Terengganu, Malaysia. Interviews with semi-structured questions were used to collect data and analyzed thematically. All the themes and sub-themes were organized using NVivo 12 software. The data show that the predominant topic in teachers' thoughts on the importance of Google tools was the reasons for their absence of use. There were two essential sub-themes: a lack of skills and proficiency and a need for more awareness of how to use Google tools. Furthermore, this study highlighted personal support of module development as a secondary theme which included two sub-themes: agreement with the need for modules and the importance of providing them. This study also underlined the importance of module preparation which was reinforced by two sub-themes: facilitating teachers' implementation of online teaching and serving as a significant reference for teachers. This study shows that effective online education requires competency, skills and knowledge of Google Tools. It suggests creating a Google Tools module to guide and serve as a resource for Malay language teachers.